Influence of Foreign Debt (Foreign Debt), Foreign Investment (PMA) and Exports to Indonesia’s Economic Growth - Otniel Malau (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2020)
This study aims to determine the effect of foreign debt, investment, exports on Indonesia's economic growth. The variables analyzed consisted of Foreign Debt, Foreign Investment, and Exports as independent variables while the dependent variable was Indonesia's economic growth variable. The analysis tool uses Multiple Regression with the Eviews 9.0 application. Based on the results of the analysis of foreign debt, it has a positive and significant effect on Indonesia's economic growth. Foreign investment has no positive and significant effect on Indonesia's economic growth. Meanwhile, the export variable has a positive and significant effect on the economic growth variable in Indonesia. Based on the results of the F test, simultaneous foreign investment and exports have a positive and significant effect on Indonesia's economic growth. Indonesia still cannot be separated from the need for foreign debt, it is better to use foreign debt to increase domestic production factors so as to provide a source of income and encourage foreign investors to invest and create a conducive climate for domestic investors because of the amount of investment in now very influential for the future and actively carrying out export activities according to research will make a positive contribution to GDP growth.